Pd(II)/(S)-t-BuPyOx-catalyzed asymmetric addition of arylboronic acids to N-sulfonyl-arylaldimines. (25th May 2021) - Song, Kaixuan; Wen, Min; Shen, Kai; Fan, Chaogang; Yang, Zhenyu; Lin, Shaohui; Pan, Qinmin
Graphical abstract: Highlights: Highly enantioselective Pd(II)-catalyzed addition to arylaldimines. ( S )- t -BuPyOx ligand application in asymmetric addition. Air and moisture insensitive reaction. 92–99% ee achieved in 9 of 16 examples. Abstract: The asymmetric version of Pd(II)/bipyridine-catalyzed nucleophilic addition of arylboronic acids to N -sulfonyl arylaldimines was developed, and excellent asymmetric induction was achieved by the use of chiral pyridinooxazoline ligand ( S )- t -BuPyOx . Moisture and oxygen-insensitive catalysis was realized under mild conditions, and 9 out of 16 examples gave 92–99% ee.